The Development of a Service Delivery Improvement Model for the Malaysian Hotel Sector: A Focus on the Developing, Formulating, Synthesising and Refinement of a New Model / Barry O'Mahony ... [et al.] - O'Mahony, Barry; Lahap, Johanudin; Sillitoe, Jim (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
The hospitality and tourism industry make a significant contribution to the economic development of many countries with some being reliant on tourism as a major catalyst for growth and development. This is the case in Malaysia where the tourism industry has been hosting large numbers of tourists arriving for business or vacation purposes as well as transient passengers en-route to other destinations. Indeed in 2009, the hospitality and tourism sector contributed RM26.6 billion towards the Malaysia Gross Domestic Product (GDP) and it was ranked second, after the manufacturing sector, in terms of overall economic contribution (Ministry of Finance/Central Bank of Malaysia, 2010). The Malaysian hotel industry has experienced significant growth in the last 10 years and many hotels in Malaysia are now opulent, with new hotels achieving the highest standards of presentation. However, service delivery often lags behind the physical environment and struggles to meet international standards and therefore the expectations of international guests. There are diverse views among service quality researchers as to how to improve service delivery standards. This paper seeks to examine an appropriate service delivery improvement model that provides a framework that can be used to attract, train, motivate and retain employees. The main arguments relate to the means to achieve customer satisfaction and to develop customer loyalty. The general view among scholars is that there is a link between employee satisfaction and job performance. This is evident within the literature where many strategies that have been developed to enhance both products and services in a variety of contexts are presented.